Eyes Wide Shut: Primary Process Opens Up - Bruxelmane, Justine; Shin, Jonathan; Olyff, Giulia; Bazan, Ariane (Frontiers in Psychology, 2020)
Freud was the first to invite his patients to lie down on a couch, facilitating the closing of the eyes. If the mere fact of closing the eyes favors access to unconscious materials, it should also favor primary process mentation. Primary process is an associative mode of thought based on superficial similarities including phonology, while secondary process mentation in language is primarily concerned with meaning. 52 participants were given French Word Lists with phonological choices (P) corresponding to primary processes while semantic choices (S) represent secondary processes when they are in mutual competition (PS). For example, participants were given a first word, such as e.g. calle (to hold) and then had to choose between lac (P; lake) and fixe (S; fix) which alternative was most similar to the first word, calle. Two control lists, SN and PN, where the other choice is unrelated (N for nothing), verify that the subjects are equally capable of recognizing the phonological and semantics similarity. Results show a ca. 10% increase in P-choices in PS when participants close their eyes, while results on PN and SN were unchanged. The mere fact of closing the eyes induces a modest increase in primary process mentation. Based on literature, the eyes closed condition is linked to increased alpha synchronisation, which is thought to induce an inward mental shift. This research contributes to validating the psychoanalytic technique consisting on inviting patients to lie down on a couch and invite them to close their eyes.